HUBUNGAN KESIAPAN BELAJAR DENGAN PRESTASI BELAJAR MATA KULIAH MICROTEACHING MAHASISWA PENDIDIKAN MATEMATIKA UNIVERSITAS SULAWESI BARAT - Nenny Indrawati; Ismail Ismail (PEDAMATH: Journal on Pedagogical Mathematics, 2018)
Learning readiness are categorized as affective learning. This correlational research aims to analyze the correlation of Learning readiness and learning achievement of mathematics education semester VIII students towards microteaching subject at West Sulawesi University. The research manipulates correlational research method with observational analysis and cros sectional approach. The research object is 31 students of mathematics education semester VIII. The technique of data analysis is simple correlational analysis and simple regressive analysis. This research shows that: (1) there is a positive and significant correlation between emotional quotient and learning achievement 0,526, (2) Regression equation is Y = 42,398 + 0,483X2